Home-made detection device for a mixture of ethanol and acetone - Amnat Reungchaiwat (2018)
A device for the detection and determination of ethanol and acetone was constructed, consisting of a packed column, a chamber with a sensor head, 2 dc power supplies, a multimeter and a computer. A commercially available TGS 822 detector head (Figaro Company Limited) was used as the sensor head. The TGS 822 detector consists of a SnO2thick film deposited on the surface of an alumina ceramic tube which contains a heating element inside. An analytical column was coupled with the setup to enhance the separation of ethanol and acetone before they reached the sensor head. Optimum system conditions for detection of ethanol and acetone were achieved by varying the flow rate of the carrier gas, voltage of the heating coil (VH), voltage of the circuit sensor (VC), load resistance of the circuit sensor (RL) and the injector port temperature. The flow of the carrier gas was 15 mL/min; the circuit conditions were VH= 5.5 V, VC= 20 V, RL= 68 k; and the injection port temperature was 150°C. Under these conditions the retention times (tR) for ethanol and acetone were 1.95 and 0.57 minutes, respectively. Calibration graphs were obtained for ethanol and acetone over the concentration range of 10 to 160 mg/L. The limits of detection (LOD) for ethanol and acetone were 9.25 mg/L and 4.41 mg/L respectively. © 2007 by MDPI.